Right ventricular pseudoaneurysm in a young adult following right heart catheterization: a rare case report and review of the literature - Habib Ahmad Esmat; Naim Ceylan; Emre Demir; Akın Çinkooğlu (The Egyptian Journal of Radiology and Nuclear Medicine, 2021)
Abstract Background Right ventricular pseudoaneurysm is an extremely rare finding than left ventricular pseudoaneurysm, associated with high mortality. The diagnosis of right ventricle pseudoaneurysm is often challenging because of its rarity and lack of typical clinical features. However, advanced cardiac imaging techniques including CT angiogram and MRI can help a timely diagnosis to avoid a fatal outcome. Case presentation The authors present the imaging findings of a right ventricular pseudoaneurysm in a 33-year-old male, presented with dyspnea and chest pain after exertion for 2 weeks. The gated CT and cardiac MRI showed a small outpouching from the right ventricle apex into the pericardial space, consistent with a pseudoaneurysm. He underwent cardiac surgery and pseudoaneurysm resection with a favorable outcome. Conclusion Right ventricular pseudoaneurysm is a very rare complication following right heart catheterization and a potentially life-threatening condition that requires prompt diagnosis and management. Though the lack of its typical clinical presentation is often a diagnostic challenge, advanced cardiac imaging techniques including CT angiogram and MRI may help a timely diagnosis to avoid a fatal outcome.